Right-sided descending colon with necrotizing enterocolitis: a rare case report - Wang, Ting; Xia, Shunlin; Liu, Mengxu; Zhang, Youcheng; Liu, Yu (Frontiers in Pediatrics, 2025)
BackgroundAnatomical variations of the colon are commonly reported, with the majority involving the right colon. However, anomalies affecting the left colon, particularly the descending colon, are rarely described in the literature.MethodsWe reviewed the clinical records of right-sided descending colon with necrotizing enterocolitis involvement at our hospital, detailing the patients’ onset, imaging studies, complications, and treatment.ResultsA newborn experienced repeated vomiting. Upper and lower gastrointestinal imaging revealed gastroesophageal reflux, the right-sided descending and sigmoid colon. Two weeks later, the infant developed NEC, and after failure of conservative treatment, surgical intervention was performed. We found that the descending colon was fixed to the posterior abdominal wall, extending from the splenic flexure toward the right side and crossing the midline. The entire colon is dilated with thickened walls. Extensive mucosal ulceration is present, accompanied by transmural necrosis. Postoperative pathology reveals significant infiltration of inflammatory cells. The most severely affected regions were the descending and sigmoid colon. Consequently, a total colectomy with end ileostomy was performed, while the distal part of sigmoid colon was preserved. Postoperatively, the newborn recovered well.ConclusionThis case may help raise awareness among surgeons regarding the variability in the position of the descending colon. It is essential to consider such anatomical variations before performing related procedures in this area, to enhance surgical safety and avoid colonic injury.